2018
DOI: 10.1016/j.clcc.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Regorafenib With 2/1 Schedule for Patients ≥ 75 Years With Metastatic Colorectal Cancer (mCRC) After Failure of 2 Lines of Chemotherapy

Abstract: Regorafenib administered with a modified 2/1 schedule to patients who were aged ≥ 75 years and non-frail with treatment-refractory mCRC seems to be tolerable and achieve encouraging results in terms of PFS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This compares favorably with similar reported studies. 13,15 Our subgroup analysis confirmed that performance status is one of the most important factors in regorafenib efficacy. All prior pivotal studies included only patients with PS 0 to 1, while one-third of our patients had PS more than one with a significant difference in PFS and OS (P = .0002 and .01, respectively) on both univariate analysis and multivariate analysis (P = .0097 and .0065, respectively).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This compares favorably with similar reported studies. 13,15 Our subgroup analysis confirmed that performance status is one of the most important factors in regorafenib efficacy. All prior pivotal studies included only patients with PS 0 to 1, while one-third of our patients had PS more than one with a significant difference in PFS and OS (P = .0002 and .01, respectively) on both univariate analysis and multivariate analysis (P = .0097 and .0065, respectively).…”
Section: Discussionsupporting
confidence: 71%
“…Similar results in PFS have been reported with either retrospective single institution or small prospective studies. 13,14 The median OS in our cohort was 8 months, which also might be related to the short follow-up duration (median, 6.3 months). This compares favorably with similar reported studies.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Nevertheless, the incidence of adverse events related to regorafenib in patients over 80 years might require treatment adaptation. A recent alternative regimen of regorafenib 2 weeks-on treatment and 1 week off was evaluated in 23 fit older patients with mCRC who progressed after oxaliplatin and irinotecan based-chemotherapy [28]. The authors reported a DCR at 2 months of 52.2%, a PFS of 4.8 months and an OS of 8.9 months.…”
Section: Discussionmentioning
confidence: 99%